Xanthomonas sp. L019 inhibition by bacteriophage isolated from wild rice ( Oryza rufipogon ) - Hoang Luan, Nguyen; Anh Thi, Nguyen Pham; Thi Giang, Tran; Bich Van, Truong Thi (Academia Journal of Biology, 2025)
Bacteriophages are widely distributed in ecosystems, facilitating isolation. The study reported 16 phage strains capable of infecting Xanthomonas sp. L019. The host spectrum survey showed that phage strain B22 infected all 8 host bacterial strains; phage strains 13 and SR1 infected 6 bacterial strains, including Xanthomonas sp. (L19, 12280), Erwinia carotovora (TCDT3), and Ralstonia spp. (OT6, OT4, OT1); phage strains 21, PCR1, and TCDT7 infected 5 bacterial strains, including Xanthomonas sp. (L19, L20, 12280), E. carotovora (TCDT3), and Ralstonia sp. (OT6); and phage strains 2B2 and SR10 infected 4 bacterial strains, including Xanthomonas sp. (L19, 12280), E. carotovora (TCDT3), and Ralstonia sp. (OT6). The study of the lysis pattern of phage strains 13, 21, 3B and B22 showed the formation of clear lysis patterns, typical of lytic phage strains. The turbidimetry assay showed significant phage strain lysis, as indicated by reduced OD values. Investigation of the effect of phage on bacterial density showed that phages reduced it by approximately 1 log CFU/mL. The biofilm degradation test demonstrated significant control by all 4 phage strains against Xanthomonas sp. L019. Phage 13 exhibited the most optimal lytic ability across all 5 time points, reducing bacterial density to 5.88 log CFU/mL and biofilm OD to 0.24, compared to the control value of 0.6. These results highlight the potential of phages as alternative therapeutics, affirming their effectiveness in controlling pathogenic bacteria and contributing to green, sustainable agriculture.